Personalidad y liderazgo: análisis teórico de su relación - Manosalvas, Carlos (2017)
This study analyzes, from a theoretical point of view, the possible relationship between personality traits and leadership style within an organization, in order to determine any causal link between them. Through a literature review of indexed scientific articles in databases such as Proquest, Science Direct, Springer Link and EbscoHost, the most widespread concepts about styles of transformational and transactional leadership and the model of the five personality factors are discussed (BIG FIVE),one of the most used models to measure this attribute. Subsequently, they study examining the relationship between these factors in various contexts, and then make a critical analysis of these investigations, from the perspective of the authors of this article and other researchers who have analyzed similar issues are discussed. Finally some considerations related to how to assess personality traits and leadership styles within organizations, an aspect of great importance for managers responsible for managing human talent, are presented. In addition, we made certain recommendations regarding future research that academics and specialists in the field of Leadership, Personality, Organizational Behavior and Human Talent could developed.